Answer:
( 11 -6)
( -5 6 )
Step-by-step explanation:
Multiply the first row of N by first column of M. This will give the first element in top row of the answer :-
-3*-2 + 1*5 = 11
Then multiply the first row in N by the second column of M to give the second element of the top row.
-3*0 + 1*-6 = -6
Then do a similar process with the second row in N.
<span> Given polynomial x^2+8x-48 = 0</span>
<span>x^2+12x-4x-48 = 0</span>
<span>x(x+12)-4(x+12) = 0</span>
<span>(x+12)(x-4) = 0</span>
<span>x+12 = 0</span>
Subtract 12 from each side.
<span>x+12-12 = 0-12</span>
<span>x = -12</span>
<span>and x-4 = 0</span>
Add 4 to each side.
<span>x-4+4 = 0+4</span>
<span>x = 4</span>
<span>Roots are -12,4.</span>
Answer:
490 or 500
Step-by-step explanation:
If we round to the 10th, Julie ran 490 feet.
I we round to the 100th, Julie ran 500 sq. ft.